FOLLOW-UP CASES OF BEDAQUILINE IN XDR-TB PATIENTS: A CASE SERIES - Malek, Shahenaz; Sinha, Anita; Singh, Anil (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Tuberculosis has consistently maintained its lead position in being among the top 10 causes by means of single-cause etiology for death among infectious disease patients. On top of it, now multi-drug resistant cases of tuberculosis (MDR-TB) are raising concern. The vision of tuberculosis eradication gets a major setback with a total of 206,030 million cases being reported worldwide with MDR or rifampicin-resistance MDR-TB in 2019. Bedaquilline a relative recent drug is being made available for the treatment of MDR and extensive drug resistance (XDR) TB under NTEP. It is being provided as a part of 2nd line of drug therapy. Regarding the drug’s efficacy and safety profiling Bedaquiline has been under extensive clinical trials at medical institutes and hospitals of reputation at national level. The treatment options available to treat XDR-TB remain extremely limited at the cost of being less effective, expensive and with more side effects. Even after the availability of potent anti-tubercular drugs, XDR Tuberculosis is proving to be more resistant to all possible drugs available to work against it.